2010
DOI: 10.1183/09031936.00112809
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitors in pulmonary hypertension: new pathophysiology and therapeutic implications: Fig. 1—

Abstract: Pulmonary hypertension is a progressive and disabling disease with as yet unclear pathogenesis, limited treatment options and poor prognosis. This is why the discovery of new pathogenic mechanisms and therapeutic strategies are needed. Endothelial progenitor cells (EPCs) are bone marrow-derived cells involved in endothelial homeostasis, as well as physiological and pathological angiogenesis. Experimental and clinical studies have been conducted to understand the possible contribution of EPCs to the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 88 publications
(92 reference statements)
0
40
0
1
Order By: Relevance
“…Given that ECFC may contribute to angiogenesis (8,9) and also exhibit a hierarchy of functional cell surface markers, we carried out immunofluorescence analysis on sections of the MPA to examine the expression of endothelial and progenitor markers such as CD31, CD34, and CD133 in the adventitial VV to characterize the nature of the cells in the normal (control) and expanding (hypoxic) VV. Increased VV density was demonstrated by the increased numbers CD31…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that ECFC may contribute to angiogenesis (8,9) and also exhibit a hierarchy of functional cell surface markers, we carried out immunofluorescence analysis on sections of the MPA to examine the expression of endothelial and progenitor markers such as CD31, CD34, and CD133 in the adventitial VV to characterize the nature of the cells in the normal (control) and expanding (hypoxic) VV. Increased VV density was demonstrated by the increased numbers CD31…”
Section: Discussionmentioning
confidence: 99%
“…The true identity of an EPC and the cell surface markers used to identify those cells remains controversial since EPC have been isolated from different sources and different species. Generally, cell surface antigens including CD34 and CD133 (8) have been used to identify endothelial progenitor phenotype, whereas CD31 and CD105 have been used to identify endothelial-specific phenotype (1). CD31 (PECAM-1) is known to be involved in endothelial cell proliferation, intercellular junction formation, and inflammatory cell trafficking through the endothelial monolayer (24,35,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, endothelial progenitor cells (EPCs) are bone marrow derived and contribute to vascular repair. We, and others, have shown that EPCs (CD34 1 /KDR 1 /CD31 1 /CD45 2 ) are decreased in PAH (5,6). Second, circulating endothelial cells (CECs) have been discussed as potential biomarkers in PAH with or without congenital heart disease.…”
mentioning
confidence: 99%